The past, present and future of Konin Lignite Mine in central Poland - Kasztelewicz, Zbigniew; Frydrychowicz, Dagmara; Galantkiewicz, Ewa; Widera, Marek (Geologos, 2025)
The Konin region is widely considered to be the cradle of lignite mining in Poland, having probably exploited as early as the 12th century on the outskirts of the present-day town of Konin. However, not until the first half of the 20th century were lignite-rich deposits discovered. In turn, industrial lignite mining in this region was initiated by the Germans during the Second World War and has been continued by Polish crews since 1945. Thus, 80 years of Polish history of Konin Lignite Mine (KLM) will be celebrated in 2025. Over eight decades, KLM has launched several opencasts, only one of which remains at the start of 2025. During this time, hundreds of millions of tonnes of lignite (646.1 million tonnes) have been mined. In order to extract such large quantities of lignite, billions of cubic metres of water (6.14 billion m3) and overburden (3.59 billion m3) had to be pumped out and removed, respectively. In this way, the natural environment in the vicinity of Konin was strongly transformed geologically, hydrogeologically and geomorphologically. The results of these changes include numerous anthropogenic hills (external dumps) and water reservoirs (mining lakes). They, along with other post-mining areas, have been subject to reclamation since at least the 1970s. KLM is carrying out reclamation works in the following directions: water, forest, agricultural, recreational, etc. It is currently expected that lignite mining in the Konin region will most likely end in 2026–2027.